Semiotic connotations in the Arabic novel The Baghdad Morgue, for example - Iraby, Itidal Salman; Abdel Shaheed, Sura Saleem (Journal of Arabic Language Sciences and Literature, 2023)
The Iraqi novel attained a very high status, in terms of the richness of events and the acceleration of changes, in addition to the fact that the Iraqi novel transcended the stages of conformation, formation and simulation. All that was the reason to delve into the midst of the Iraqi novel, and we saw the novel (Baghdad Morgue) and interrogated the secrets of the narrative text according to the semiotic approach; which is one of the curricula that has proven its presence in the monetary arena as a school with its own curriculum and foundations. * What role does semiotics play to show the effectiveness of the novel and its impact on the recipient? * Did the selected novel succeed in raising political, cultural and critical issues? The research will show the ability of the Iraqi novelist to employ connotations that reflect the state of crisis in society, and how the semiotic approach works on it through applications that reflect its significance.